(untitled) (International journal of artificial intelligence, 2025)
This article focuses on the existing water problems in Uzbekistan and their causes. It analyzes the scarcity of water resources, climate change, inefficient water use, and infrastructure challenges. The article also discusses effective solutions for addressing the problem, including the introduction of water-saving technologies, reforms, and international cooperation. It highlights ways to use water resources rationally and ensure sustainable water supply for future generations. Furthermore, this article discusses the proper distribution and efficient management of water resources in Uzbekistan within the context of current geopolitical trends. Additionally, we will address the key principles related to water allocation in Central Asia that require our attention. Finally, we will discuss Uzbekistan's future prospects, taking into account forecasts of water resource sources and reserves.